Pilot study evaluating tolerability and changes in fecal microbiota associated with novel probiotic administration to dogs with diarrhea - Doshier, Jessi; Anderson, Brooke; Yang, Fan; Stewart, Samuel D.; Calapa, Kayla A.; Cooper, Rachel; Wilson-Robles, Heather; Embree, Mallory; Khanna, Chand (Frontiers in Veterinary Science, 2026)
BackgroundDiarrhea is one of the most common reasons for visiting canine veterinary clinics or emergency centers. Common treatment approaches include dietary modification, antibiotics, and/or probiotics, which are frequently initiated empirically. Antibiotics can have detrimental long-term effects on the gut microbiome and contribute to antimicrobial resistance, prompting a need for alternative therapies. Probiotics are a promising option; however, their strain-specific effects on the canine gut microbiome have been insufficiently characterized in vivo, particularly in dogs with diarrhea.Hypothesis/objectivesThis study aimed to evaluate tolerability and changes in fecal microbiota in dogs with diarrhea during the administration of a novel, advanced microbiome-derived probiotic (AMP) consisting of live Peptacetobacter hiranonis, Megamonas funiformis, and Enterococcus faecium, strains of which were all originally isolated from the feces of a healthy dog.AnimalsThis single-arm, prospective observational pilot study consisted of 11 client-owned adult dogs of various breeds presenting for chronic diarrhea (>5 days) with a Purina Fecal Score (PFS) between 4 and 7.MethodsTolerability of the AMP was assessed through serial clinical examinations and comparison of PFS to baseline. Dogs were classified as responders if their PFS improved to <4 by day 7, and as non-responders otherwise. Fecal samples collected at baseline, day 7, and day 56 of AMP administration underwent Illumina amplicon next-generation sequencing (NGS) of 16S rRNA gene fragments (V4 region) to assess the fecal microbiome composition and diversity in each patient.ResultsNo adverse events were noted in any dogs receiving the AMP. Clinical improvement in diarrhea was noted in eight of 11 dogs after administration of the AMP. Increases in fecal microbiome alpha-diversity were observed after 1 week of AMP administration for six out of seven long-term participants.Conclusion and clinical importanceThis pilot study indicates that the AMP was well tolerated in dogs with diarrhea, with dogs maintaining or improving clinical appearance during administration. These preliminary findings justify larger controlled studies to evaluate AMP efficacy and to explore associations between treatment, fecal microbiome changes, and clinical response.Clinical trial registrationIdentifier: VCT23005615.